COMPARING DIFFERENT STRATEGIES IN IMPROVING STUDENTS READING COMPREHENSION - Wahid Hasim (English Education and Applied Linguistics Journal (EEAL Journal), 2018)
This research entitled comparing different reading strategies in improving students’ reading comprehension was conducted to find whether there is a significant difference in students’ reading comprehension based on the different strategy given to the students. Quantitative research was employed in doing the research by using one shot design framework. The treatment was conducted for 3 weeks in 5 different classes. The research was done in a private university in Garut. The population was 5 classes of third grade students enrolled in Reading III subjects. 45 students consisting 9 students from each class were taken as the sample by using cluster random sampling technique. Statistical computation carried out in the research was ANOVA. From the analysis it was found out that the F ratio (4.48) value is higher than the critical value (2.61) which led to the conclusion that there is significant different in student reading comprehension by using different reading strategies